Arrhythmias: Its Occurrence, Risk Factors, Therapy, and Prognosis in Acute Coronary Syndrome - Khanal, Raja Ram; Gajurel, Ratna Mani; Shah, Sangam; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev (Journal of Nepal Health Research Council, 2023)
Background: Patients with acute coronary syndrome may lead to various metabolic and electrophysiological changes that induce both asymptomatic and symptomatic life-threatening arrhythmias, which increases morbidity and mortality. Methods: This observational retrospective study was conducted at Manmohan Cardiothoracic Vascular and Transplant Center, Institute of Medicine, Maharajgunj, Kathmandu, Nepal. Three hundred ninety-five patients with a diagnosis of acute coronary syndrome were enrolled in the study. Results: A total of 395 patients were included in the study with a mean age of patients 61.29± 13.5 years and with male predominance. A total number of 115 cases of arrhythmia were recorded among which the most common were atrioventricular block (10%), reperfusion arrhythmia (9.6%) followed by ventricular premature complex (8%), atrial fibrillation/flutter (6%), and ventricular tachycardia/fibrillation (5%). There was a significant difference in the incidence of arrhythmia in acute coronary syndrome group. STEMI (39.7%), NSTEMI 26(20.8%) and unstable angina11(14.8%) respectively (p=<0.001). Reperfusion arrhythmia was present in 89.47% of STEMI and 10.4 % of NSTEMI/ unstable angina and was statistically significant (p-value <0.001). A total of three patients (0.7%) needed permanent pacemaker insertion in the acute coronary syndrome group. All of these patients were STEMI which was 1.5% of total STEMI, two in inferior wall STEMI (2.6%) and 1 in anterior wall STEMI (0.8%). The total in-hospital mortality was 20 (5.06%), 17(8.6%) among STEMI and 3(2.4%) among NSTEMI, and none in unstable angina (P =<0.001). Pulmonary edema (12.9%) was the most common in-hospital outcome followed by cardiac arrest (7.6%).Conclusions: Arrhythmia in acute coronary syndrome is a common problem and may lead to structural and functional impairment of myocardial function. Keywords: Arrythmias; coronary artery disease; STEMI